Optical microfiber sensor coated with nanomaterials for ammonia sensing applications - Girei, Saad Hayatu (2021)
Ammonia (NH3) is a colorless compound with a distinctive odor composed of nitrogen and hydrogen atoms that can be found in water as ammonia nitrogen (NH3-N) and in the air as NH3 gas. It is commonly used in several industrial processes, agricultural activity and several biological systems. However, at high concentrations, NH3 can be toxic to plants, animals as well as human beings. Its detection is important for environmental and industrial safety. The previous development of NH3 sensors were mostly concentrated on the thick films and electrical based sensors rather than optical. In recent years, tapered optical microfibers sensors have been attracting greater attention due to their simplicity and immunity to various sources of interferences. This research work presents the development of a tapered optical microfiber sensor coated with nanomaterials for the detection of NH3 in liquid and gaseous forms. The working principle of the sensor is based on the interaction between the evanescent fields of the tapered microfiber and different NH3 concentrations. The interactions alter the properties of light propagating through the optical fiber and consequently producing a measurable response that allows quantifying the concentration of NH3. To enhance the sensing performance of the developed sensor, zinc oxide (ZnO) and graphene oxide (GO) nanomaterials were deposited on the fiber surface providing a higher surface area and suitable chemical reaction between NH3 and the sensing layer. The GO nanostructures and ZnO nanorods were deposited using the optical and hydrothermal deposition techniques, respectively. The optical deposition technique was successfully implemented to produce uniform GO coating with corrugated and wrinkled structures on the cylindrical optical microfiber surface. The GO deposition is due to the occurrence of the thermophoresis effect resulting from the interaction of optical radiation with the GO solution at the tapered area of the microfiber interferometer (MFI). A unique hydrothermal method is designed for uniform coating around the cylindrical optical microfibers. This method is a simple and environmentally-friendly deposition technique that produced ordered arrays of ZnO nanorods directing outwards from the surface of the tapered optical microfiber. The NH3-N sensing response investigated in a wide wavelength range of 1500 – 1800 nm by monitoring the wavelength shift shows sensitivities of 0.0894 nm/ppm and 0.1748 nm/ppm at 1785 nm for bare and GO-coated MFI sensor, respectively. The developed NH3-N sensor showed excellent properties of high sensitivity, stability, and fast response at room temperature as compared to the conventional sensors. The ZnO nanorods and GO-coated optical microfiber sensor for NH3 gas exhibit maximum absorbance response with the optimum sensing layer thickness of 750 nm and 692 nm, respectively. Sensing performance results reveal the sensitivities of 59.18 AU/% and 61.78 AU/% for sensors coated with ZnO nanorods and GO, respectively. The results of this investigation further reveal a promising method to improve NH3 gas sensitivity by prolonging the hydrothermal growth duration of ZnO nanorod arrays on the optical microfiber. It was also discovered that the GO-coated sensor produced negative and positive absorbance responses at the visible and near-infrared wavelength regions, respectively. These interesting sensing characteristics provide a new understanding of the behavior of absorbance response of the GO-coated sensor to the operational bandwidth. Above all, the combination of appropriate sensitive materials and optical fiber devices provides a convenient platform to detect the chemical concentrations of liquid and gas. As a result, these sensors may find applications in the manufacture of fertilizer, medical diagnostics, and in rivers and drinking water monitoring.